1985
DOI: 10.1523/jneurosci.05-03-00617.1985
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and serotonergic innervation of physiologically identified cells of the guinea pig's myenteric plexus

Abstract: Ganglion cells of the myenteric plexus of the guinea pig were physiologically classified as to cell type using intracellular microelectrodes containing horseradish peroxidase (HRP). lnterganglionic fiber tracts were then stimulated in an attempt to elicit slow excitatory postsynaptic potentials (EPSPs) in the impaled cells. The presence or absence of a slow EPSP was noted, following which the cells were injected with HRP through the recording micropipette and finally were incubated with tritiated 5-hydroxytryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 41 publications
3
72
0
Order By: Relevance
“…The other AH neurons are also presumed not to supply the muscle. AH neurons receive morphologically identifiable synapses (Erde et al, 1985;Llewellyn-Smith et al, 1988a;Pompolo and Fumess, 1988), but this study indicates that few, if any, of these are likely to be SPimmunoreactive. However, each AH cell undoubtedly receives a large number of ultrastructurally unspecialized contacts from SP-positive vesiculated nerve fiber profiles, since this is the case for all myenteric neurons.…”
Section: Vesicles In Sp-immunoreactive Nerve Fibersmentioning
confidence: 62%
See 1 more Smart Citation
“…The other AH neurons are also presumed not to supply the muscle. AH neurons receive morphologically identifiable synapses (Erde et al, 1985;Llewellyn-Smith et al, 1988a;Pompolo and Fumess, 1988), but this study indicates that few, if any, of these are likely to be SPimmunoreactive. However, each AH cell undoubtedly receives a large number of ultrastructurally unspecialized contacts from SP-positive vesiculated nerve fiber profiles, since this is the case for all myenteric neurons.…”
Section: Vesicles In Sp-immunoreactive Nerve Fibersmentioning
confidence: 62%
“…Between 10 and 35% of myenteric neurons belong to this group (Furness and Costa, 1987). These neurons have large, smooth cell bodies (Dogiel Type II morphology), are usually located centrally within the ganglia, and often give rise to several long processes (Bomstein et al, 1984a;Erde et al, 1985;Iyer et al, 1988). About 85% of AH neurons are immunoreactive for calcium binding protein (calbindin D 28K) and do not provide terminals to the muscle (Furness et al, 1988a;Iyer et al, 1988).…”
Section: Vesicles In Sp-immunoreactive Nerve Fibersmentioning
confidence: 99%
“…Similar to CNS astrocytes, many EGC processes display small swollen end-feet that make contact with the basal lamina that surrounds the ganglia or with neighboring blood vessels (Erde et al, 1985;Hanani and Reichenbach, 1994). Two different morphologies have been ascribed to EGC depending on their location within the plexus.…”
Section: Localization and Phenotypic Characteristics Of Egcmentioning
confidence: 99%
“…Those few ChAT or tachykinin-IR cells that were apposed by 5-HT-IR boutons were not prominent. Synaptology and thus the function of serotoninergic fibers emerging from serotoninergic descending interneurons has not been clarified yet since the reports that investigated the problem published different results (Erde et al, 1985;Young and Furness, 1995;Neal and Bornstein, 2007). Erde et al (1985) reported that mainly type II/AH neurons considered sensory neurons were contacted by serotoninergic terminals.…”
Section: A Possible Enteric Circuit Underlying Serotonin-tachykinin Imentioning
confidence: 99%
“…Synaptology and thus the function of serotoninergic fibers emerging from serotoninergic descending interneurons has not been clarified yet since the reports that investigated the problem published different results (Erde et al, 1985;Young and Furness, 1995;Neal and Bornstein, 2007). Erde et al (1985) reported that mainly type II/AH neurons considered sensory neurons were contacted by serotoninergic terminals. According to Young and Furness (1995), Dogiel type II neurons received a few serotonin inputs and none of them formed synapses, whereas the highest number of serotonin terminals were related to Dogiel type I neurons.…”
Section: A Possible Enteric Circuit Underlying Serotonin-tachykinin Imentioning
confidence: 99%